Post-Natal Gestational Age Assessment Using Sonographic Measurement of Femoral Length - Deka, Anupama; Manoj, G.M.; Prabhu, B.J. (Journal of Nepal Paediatric Society, 2017)
Introduction: An accurate Gestational Age (GA) is a better predictor of neonatal outcome than birth weight. GA assessment has many diagnostic and therapeutic importance. The methods available for GA estimations are LMP, new Ballard score and each methods has its own drawback which makes them either over estimate or under estimate GA. Antenatal 2nd trimester ultrasound measured femoral length gives more accurate GA estimation. Using similar principles we hypothesized that biometry of long bones with sonography imaging is feasible after birth and may be used to assess GA. The objectives of this study were to assess Post-natal gestational age using sonographic measurement of femoral length and then compare values with antenatal standards and further comparison of validity of each value with gestational age assessment by new Ballard score and the GA by LMP. Material and Methods: Ninety neonates from 32 weeks to 40 weeks of GA according to accurate LMP were subjected ultrasonographic measurement of femoral length. Results: GA calculated using accurate LMP as standard and compared with GA calculated from New Ballard score over estimated the GA. Post natal femoral length measured using sonographic method showed increase in femoral length with increasing GA similar to antenatal femoral standard and showed no statistical difference (p-value 0.375). Conclusions: post natal femoral length measured by ultrasonographicaly is a safe, feasible, objective and fastest method of GA estimation. J Nepal Paediatr Soc 2016;36(3):268-272